p.R270X MECP2 mutation and mortality in Rett syndrome - Jian, Le; Archer, H.; Ravine, D.; Kerr, A.; De Klerk, N.; Christodoulou, J.; Bailey, M. (Nature Publishing Group, 2005)
Among cases in the Australian Rett Syndrome Database, the nonsense mutation p.R270X is one of the most commonly occurring single pathogenic MECP2 mutations. In two recent published reports of the MECP2 mutational spectrum the p.R270X appeared to be under represented. We hypothesised that increased mortality arising from this mutation may underlie this apparent discrepancy. We investigated our hypothesis in two independent study groups from Australia and the UK with prospective data collections (total n=524). Only females with Rett syndrome and an identified MECP2 mutation were included. Significant differences in survival were detected among Rett syndrome cases grouped for the eight most frequent mutations (log-rank v2 (7)=15.71, P=0.03). Moreover, survival among cases with p.R270X, when compared with survival among cases with all the other mutations was reduced (log-rank v2 (2)=6.94, P=0.01). Our observation of a reduced survival associated with the p.R270X mutation offers an explanation for the under representation of p.R270X in older subjects with Rett syndrome.